Linking Millennium Cohort data to birth registration and hospital episode records. - Hockley, C; Quigley, M; Hughes, G; Calderwood, L; Joshi, H; Davidson, L (2008)
The Millennium Cohort Study of 18,818 UK babies born in 2000-02 interviewed parents when the baby was 9 months old. Time constraints on the interview limited the amount of health-related questions that could be included. The aim of this study was to augment interview data with information from birth registrations and hospital records. It also provided an opportunity to assess the accuracy of the data acquired and parents' recall of the information on pregnancy and delivery. Deterministic and probabilistic matching were used to obtain information from birth registration and hospital records. Investigation into the accuracy of the matches obtained was undertaken. The records received were checked for range, consistency and completion. Birth registration data were obtained for 99% of those who gave consent. The number of additional variables gained ranged from six in Northern Ireland to 16 in Scotland. Hospital record data were obtained for 83% of those who gave consent. The additional general and maternity-related variables gained ranged from 55 in Scotland to 76 in England. Completion of available health record variables ranged from 28% to 100% across all UK countries. Linkage to birth registration and hospital records in order to augment Millennium Cohort Study data with routinely collected data was successful. The variables gained by linkage have added considerable value to the cohort study and validated some of the mother's responses.